Initiation of Tocilizumab or Baricitinib Were Associated With Comparable Clinical Outcomes Among Patients Hospitalized With COVID-19 and Treated With Dexamethasone - Wong, Carlos K. H.; Lau, Kristy T. K.; Au, Ivan C. H.; Xiong, Xi; Chung, Matthew S. H.; Leung, Belle Y. C.; Lau, Eric H. Y.; Cowling, Benjamin J. (Frontiers in Pharmacology, 2022)
Objectives: This retrospective cohort study aims to explore head-to-head clinical outcomes and complications associated with tocilizumab or baricitinib initiation among hospitalized COVID-19 patients receiving dexamethasone. Methods: Among 10,445 COVID-19 patients hospitalized between January 21st 2020 and January 31st 2021 in Hong Kong, patients who had received tocilizumab (n = 165) or baricitinib (n = 76) while on dexamethasone were included. Primary study outcome was time to clinical improvement (at least one score reduction on WHO clinical progression scale). Secondary outcomes were disease progression, viral dynamics, in-hospital death, hyperinflammatory syndrome, and COVID-19/treatment-related complications. Hazard ratios (HR) of event outcomes were estimated using Cox regression models. Results: The initiation of tocilizumab or baricitinib had no significant differences in time to clinical improvement (HR = 0.86, 95%CI 0.57-1.29, p = 0.459), hospital discharge (HR = 0.85, 95%CI 0.57-1.27, p = 0.418), recovery without the need for oxygen therapy (HR = 1.04, 95%CI 0.64-1.67, p = 0.883), low viral load (HR = 1.49, 95%CI 0.85-2.60, p = 0.162), and positive IgG antibody (HR = 0.97, 95%CI 0.61-1.54, p = 0.909). Time to viral clearance (HR = 1.94, 95%CI 1.01-3.73, p = 0.048) was shorter in the tocilizumab group with marginal significance, compared to that of baricitinib. Meanwhile, the two treatment modalities were not significantly different in their associated risks of in-hospital death (HR = 0.63, 95%CI 0.29-1.35, p = 0.233), severe liver injury (HR = 1.15, 95%CI 0.43-3.08, p = 0.778), acute renal failure (HR = 2.33, 95%CI 0.61-8.82, p = 0.213), hyperinflammatory syndrome (HR = 2.32, 95%CI 0.87-6.25, p = 0.091), thrombotic and bleeding events (HR = 1.39, 95%CI 0.32-6.00, p = 0.658), and secondary infection (HR = 2.97, 95%CI 0.62-14.31, p = 0.173). Conclusion: Among hospitalized patients with moderate-to-severe COVID-19 on background dexamethasone, the initiation of tocilizumab or baricitinib had generally comparable effects on time to clinical improvement, hospital discharge, recovery, low viral load, and positive IgG antibody; risks of in-hospital death, hepatic and renal complications, hyperinflammatory syndrome, thrombotic and bleeding events, and secondary infection. On the other hand, tocilizumab users might achieve viral clearance slightly faster than baricitinib users. Further studies and clinical trials are needed to confirm our findings regarding the evaluation of tocilizumab and baricitinib in COVID-19 patients with different disease severities, at varying stages or timing of drug initiation, and considering the concomitant use of other therapeutics.